Neotropical Entomology - Neotropical Entomology (Springer Nature, 2026)
Neotropical Entomology is an international journal devoted to fundamental and applied research in Entomology and Acarology with a focus on Neotropical fauna. Fauna from other regions are welcome as long as their impact is internationally relevant.
FI 0.7
Q2
Keywords: Life Sciences; Entomology; Entomología; Acuerdos transformativos; Transformative agreements; Entomología y acarología de la fauna neotropical; Ecología, comportamiento, fisiología, biología y manejo de plagas; Control biológico, entomología médica y veterinaria, y sistemática aplicada